Counseling Teacher Solutions in Conflict Management - Haetami, Haetami; Saddhono, Kundharu; Jarkawi, Jarkawi; Lahiya, Arkam; Sudadi, Sudadi (Al-Hayat: Journal of Islamic Education, 2023)
Students have a significant role in the success of a lesson. Students' success is in the hands of educators who guide them to understand, solve, make decisions, be responsible, and become independent human beings. Hence, this research focuses on Counseling Teacher Efforts, whose leading task indicator is being able to provide services to students. This study uses an interpretive paradigm through a qualitative approach, types of case studies, data collection techniques using in-depth interviews and observation, data analysis using Miles Huberman's theory, and checking the validity of the data by triangulation. This research resulted in counselling teacher guidance efforts with an emotional and spiritual quotient (ESQ) in collaboration with religion teachers (continuous subject integration) and with outbound parenting efforts through scheduled extracurriculars. This study expands its setting and orientation by integrating subjects in the process, demonstrating the role of the Counseling Teacher, as exceptional cases illustrate the need for combined training.